Validation of a Short Adherence Questionnaire for Children Living with HIV on Antiretroviral Therapy in Kenya - Rachel Christine Vreeman MD, MS; Michael Lawrence Scanlon MA, MPH; Wanzhu Tu PhD; James Slaven MS; Samuel Ayaya MBChB, MMED; Winstone Nyandiko MBChB, MMED, MPH (Journal of the International Association of Providers of AIDS Care, 2018)
Background: There are few validated tools to measure adherence for children living with HIV. We identified questionnaire items for caregivers of Kenyan children aged <15 years living with HIV. Methods: Caregiver–child dyads were followed for 6 months. At monthly visits, the child’s HIV provider administered a 10-item questionnaire to the caregiver. Children were given electronic dose monitors (Medication Event Monitoring Systems [MEMS]). Correlation between questionnaire items and dichotomized MEMS adherence (≥90% doses taken versus <90%) was investigated using logistic regression models. Results: In 95 caregiver–child dyads, mean age of children (40% female) was 8.3 years. Items associated with higher odds of MEMS adherence in multivariable analysis included the father giving the child medication, being enrolled in a nutrition program, and the caregiver reporting no difficulties giving the child medication. Conclusion: Providers typically ask about missed doses, but asking about caregiver responsibilities and difficulties in giving the child medication may better detect suboptimal adherence.